Laser based Packed Red Blood Cells Volume (PCV) Determination System (NTU Journal of Engineering and Technology, 2026)
It is common knowledge that hematology test panels include measurements of the packed cell volume (PCV), also known as the hematocrit, because they are so helpful in any hematologic workup. The packed red blood cells volume (PCV) value can be calculated in a variety of ways. Some of them use direct approaches, while others use indirect ones. The most straightforward and cost-effective method, which is frequently used as a direct means to assess PCV but has a chance of human mistake and trapped plasma, is using a manual ruler to evaluate PCV. In our search, we developed and built an electronic circuit to assess PCV that relies on the Arduino board. The novel measurement tool is made up of red laser (650 nm) emitters to take advantage of the red light's specific absorption by erythrocytes (red blood cells), which is higher than the red light's lowest absorption by blood plasma. The photocell then receives the transmitted light, and the Arduino board processes the photocell's signal. The PCV evaluation method is reliable because of the change in light intensity between the incident and transmitted light after passing through a centrifuged blood sample. The device's six lasers and photocells make it easier and more accurate to calculate the ratio of erythrocyte volume to total blood volume. Last but not least, a PCV blood analysis can be made utilizing a programmable Arduino board 2560 mega (with determined mathematical formulae that are stored in Arduino memory to calculate and screen Values).